Assessment of Think-Pair-Share Strategy on Students Self-Esteem Development in Jos North Schools, Plateau State - Shittu Lukman Olayinka (Matondang Journal, 2024)
This research aimed to assess the impact of the think-pair-share strategy on the self-esteem development of Junior Secondary School II (JSS II) social studies students in Jos North, Plateau State, Nigeria. The study was guided by four objectives, and corresponding research questions were formulated to address these objectives. A quantitative descriptive survey method was employed as the research design. The target population comprised 1334 JSS II social studies students across 22 public schools in Jos North. The researcher designed two structured questionnaires for data collection, one for students and one for teachers. Face and content validity were applied to the instruments, and reliability was established at 0.67 and 0.71 for the students' and teachers' questionnaires, respectively. Data analysis utilized mean and standard deviation for the main analysis, while simple percentages were employed to analyse respondents' demographic information. The findings indicated, among other insights, that the think-pair-share strategy was not widely known among teachers and students of social studies in the study area. Additionally, the study highlighted the significant role of the think-pair-share strategy in fostering the development and enhancement of students' self-esteem in Junior Secondary School. The study recommends organizing seminars, symposiums, and conferences to familiarize teachers with the think-pair-share strategy as an effective teaching approach. Furthermore, school administrators should recognize the importance of introducing teachers and students to the think-pair-share strategy and encourage its implementation in their respective classrooms.